Are there any Cournot industries? - David Flath (Osaka University, Institute of Social and Economic Research (ISER), 2010)
For 70 Japanese manufacturing industries, I test the simple Cournot hypothesis of proportionality between industry price-cost margin and Herfindahl index against the non-nested alternative that the industry price-cost margin remains constant in the face of varying Herfindahl index, as it would under a simple product differentiated Bertrand framework. I then test each of these against the alternative hybrid specification that nests both of them, and from the pairwise tests, compute likelihoods of each specification. The simple Cournot specification is the most likely for five of the industries, the simple Bertrand specification for 35, and the hybrid specification for 30.
Keywords: L11; L13; L60; 330; Gewinn; Produktionskosten; Konzentrationsindex; Preiswettbewerb; Duopol; Industrie; Japan